PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN TERNAK IKAN LELE DI RT 007/ RW 003 DESA BENTENG HULU KECAMATAN MEMPURA KABUPATEN SIAK - Yunifa Riska Efendi; Titi Maemunaty; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines Community Empowerment through CatfishLivestock Management at Rt 007/ Rw 003 Benteng Hulu Village, Mempura District,Siak Regency and in the Empowerment there are preparation, planning, implementationin starting the management of catfish. The purpose of the study was to identify anddescribe community empowerment through the management of catfish livestock in RT007/ RW 003 Benteng Hulu Village, Mempura District, Siak Regency. This type ofresearch is descriptive with a qualitative approach, where the data collection process iscarried out by interviewing 5 subjects, namely core informants, control informants, coreinformants 1, core informants 2, core informants 3, with documentation included. Basedon the results of interviews, researchers found 3 indicators, namely: (1) preparation, (2)planning, (3) implementation. the study of the 3 indicators, the researchers found theappropriate implementation stages in carrying out Community Empowerment throughCatfish Livestock Management.Key Words: Community Empowerment, Catfish Livestock Management